Report of the Working Group on Development of North Eastern Region During the Seventh Five Year Plan March 1985 - Planning Commission (Planning Commission, 1983)
The Working Group held its first meeting at New Delhi on 19th November 1983. It set up a Nodal Group and Four Sub-Groups for specific subjects. the Nodal Sub-Group had to study various reports and various materials relating to the North East and give general guidance, approach, strategy, priorities and objectives of development. It also envisaged that Chief Secretaries of some of the State/Union Territories of the North-East should chair the Sub-Groups so that the experience of the State Governments/UT Administrations can be drawn upon. Subsequently, some experts and Heads of Departments, dealing with subject concerned were also adopted as Members of the Sub-Groups.
The Director, Information and Public Relation, North Eastern Council